Scaffolding internet reading: a study of a disadvantaged school community in Ireland - Dwyer, Bernadette (2010)
The present study had three main purposes: first, to explore the baseline skills and strategies of struggling readers as they conducted online Internet inquiry; second, to scaffold these children to develop effective online reading comprehension and information seeking-skills and strategies in the context of an integrated curriculum; and third, to examine the affective, cognitive and social dimensions of learning in groups and the role of peer collaboration in developing online reading skills and strategies during Internet inquiry.